Dissemination patterns and chronology of distant metastasis affect survival of patients with head and neck squamous cell carcinoma. (August 2021) - Berzenji, Diako; Sewnaik, Aniel; Keereweer, Stijn; Monserez, Dominiek A.; Verduijn, Gerda M.; van Meerten, Esther; Mast, Hetty; Mureau, Marc A.M.; van der Lugt, Aad; Koljenovic, Senada; Dronkers, Emilie A.C.; Baatenburg de Jong, Robert J.; et al.
Highlights: Oligometastasis in HNSCC signifies a better prognosis than a polymetastatic pattern. Distant metastasis in HNSCC most often have an explosive-disseminating pattern. Metachronous distant metastasis occurrence is associated with a worse prognosis. Abstract: Objectives: To define metastatic categories based on their prognostic significance. We hypothesized that oligometastasis in patients with head and neck squamous cell carcinoma (HNSCC) is associated with better post-distant metastasis disease specific survival (post-DM DSS) compared to patients with polymetastasis. Furthermore, the impact on survival of synchronous versus metachronous distant metastasis (DM) occurrence was assessed. Materials and methods: Retrospective cohort study in which patients with DM were stratified into three groups: oligometastasis (maximum of 3 metastatic foci in ≤2 anatomic sites), explosive metastasis (≥4 metastatic foci at one anatomic site) and explosive-disseminating metastasis (spread to ≥3 anatomic sites or >3 metastatic foci in 2 anatomic sites). In addition, patients were divided into synchronous versus metachronous DM. Results: Between January 1, 2006 and December 31, 2013, a total of 2687 patients with HNSCC were identified, of which 324 patients developed DM. In this group, 115 (35.5%) patients had oligometastasis, 64 (19.8%) patients had explosive metastasis and 145 (44.8%) patients had explosive-disseminating metastasis. Their median post-DM DSS were 4.7 months, 4.1 months and 1.7 months respectively (p < .001). Synchronous DM was associated with more favorable survival rates in univariable and multivariable analyses than metachronous DM with recurrence of the index tumor (6-month post-DM DSS probability of 0.51 vs 0.17, p < .001). Conclusion: Oligometastasis in HNSCC signifies a better prognosis than a polymetastatic pattern. Metachronous DM occurrence with recurrence of the primary index tumor is associated with an unfavorable prognosis.